Real-Time Polymerase Chain Reaction for Microbiological Diagnosis of Parapneumonic Effusions in Canadian Children - Jeffrey M Pernica; Ioana Moldovan; Francis Chan; Robert Slinger (Canadian Journal of Infectious Diseases and Medical Microbiology)
BACKGROUND: Community-acquired pneumonia (CAP) complicated by parapneumonic effusion/empyema is an infectious syndrome commonly encountered by physicians caring for children in Canada.